Distortion analysis in axial ultrasonic assisted milling of Al 7075-T6 - Masuod Bayat; Saeid Amini (International Journal of Lightweight Materials and Manufacture, 2024)
Dimensional distortion and instability in the milling process of aluminum alloy parts can significantly increase production costs and result in defective parts. Therefore, distortion mitigation has long been a central focus of aerospace industry researchers. This article aims to investigate the effect of axial ultrasonic-assisted milling on distortion. In this study, the machining parameters effect in conventional milling (CM) and ultrasonic assisted milling (UAM) were experimentally and statistically investigated on distortion and milling force, and the results were subjected to a comparative analysis. Experiments provided compelling evidence of the technical advantages offered by axial ultrasonic-assisted milling, demonstrating its efficacy in reducing both milling force and distortion when compared to conventional milling. Furthermore, our study established a direct relationship between milling force and distortion. Applying the axial ultrasonic-assisted vibration resulted in a notable 29% reduction in cutting force compared to conventional milling. Additionally, UAM exhibited a reduction in distortion by approximately 21%. These findings have significant implications, particularly in improving the flatness tolerance of the workpiece, thereby yielding components free from waves and warpages.